2009
DOI: 10.1002/ardp.200900077
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cytotoxicity by Bioluminescence Inhibition, Antibacterial and Antifungal Activity of ([1,2,4]Triazolo[1,5‐c]quinazolin‐2‐ylthio)carboxylic Acid Amides

Abstract: We report in this work the synthesis, cytotoxicity, and antimicrobial activity of ([1,2,4]triazolo[1,5-c]quinazolin-2-ylthio)carboxylic acid amides 4-7 in connection with our previous research in the preparation of triazoloquinazoline derivatives. Due to simplicity, general availability of starting materials, and high yields, the most reliable method of synthesis appeared to be the one with N,N-carbonyldiimidazole activation stage. The chemical structures of all obtained substances were deduced from FT-IR, (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Moreover, our previous investigations in the series of similar condensed heterocycles, namely, 2-thio-[1,2,4]triazolo[1,5- c ]quinazoline derivatives, showed that ([1,2,4]triazolo[1,5- c ]quinazolin-2-ylthio)carboxylic acids and amides ( 3 ) possessed antifungal activity against Candida albicans and Aspergillus niger [26, 27]. So, the aim of this work is the purposeful formation of the tetrazolo[1,5- c ]quinazoline-5-thione skeleton, synthesis of its S-derivatives, and screening of their antibacterial, antifungal, and antitumor properties with subsequent docking studies of the most active ones.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our previous investigations in the series of similar condensed heterocycles, namely, 2-thio-[1,2,4]triazolo[1,5- c ]quinazoline derivatives, showed that ([1,2,4]triazolo[1,5- c ]quinazolin-2-ylthio)carboxylic acids and amides ( 3 ) possessed antifungal activity against Candida albicans and Aspergillus niger [26, 27]. So, the aim of this work is the purposeful formation of the tetrazolo[1,5- c ]quinazoline-5-thione skeleton, synthesis of its S-derivatives, and screening of their antibacterial, antifungal, and antitumor properties with subsequent docking studies of the most active ones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compounds 3 were characterized by the functional substituent signals at position 2, which, depending on the structure, had classical magnetic shifts and the corresponding multiplicity. [15][16][17][18] In the spectra of compounds 6 and 7, the triazoloquinazoline fragment of molecules formed a characteristic subspectrum of two one-proton doublets: H-10 at d = 8.48-8.35 ppm and H-7 at d = 7.97-7.83 ppm, and two one-proton triplets: H-8 at d = 7.85-7.60 ppm and H-9 at d = 7.67-7.60 ppm. The data indicated that the chemical shifts of these protons differed from those of the parent compounds 3 and, as expected, they significantly affected the nature of the substituent at position 5.…”
mentioning
confidence: 97%
“…[5,[15][16][17][18] Other starting materials and solvents were obtained from commercially available sources and used without additional purification.…”
mentioning
confidence: 99%
“…The marine luminescent bacteria Photobacterium leiognathi strain Sh1, isolated from the Azov Sea Shrimp, were used for the bioluminescence analysis [25, 26]. Bacteria were cultivated on a nutrient environment containing (g/L): pepton – 5, yeast extract – 1.5, meat extract – 1.5, sodium chloride – 30, pH = 7.4.…”
Section: Methodsmentioning
confidence: 99%